2017
DOI: 10.1007/s12031-017-1020-z
|View full text |Cite
|
Sign up to set email alerts
|

CD200Fc Attenuates Retinal Glial Responses and RGCs Apoptosis After Optic Nerve Crush by Modulating CD200/CD200R1 Interaction

Abstract: To explore the hypothesis that CD200Fc, a CD200R1 agonist with anti-inflammatory properties, will inhibit retinal glial cells hyperactivation and retinal ganglion cells (RGCs) apoptosis after optic nerve injury. CD200Fc was immediately administered after optic nerve crush (ONC) once by intravitreal injection. Rats were euthanized at 5 days after ONC. The density of RGCs was counted by immunostaining of retina flat mounts for Brn3a. TUNEL assay, immunoblotting analysis of ionized calcium-binding adapter molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…53 Another potential important mechanism of action of glibenclamide could be the upregulation of cd200r1, as its agonist CD200FC significantly protected ganglion cells from apoptosis in a nerve crush model. 54 The up-regulation of Bcl2a1 gene, with a strong antiapoptotic effect is in line with this hypothesis.…”
Section: Discussionsupporting
confidence: 64%
“…53 Another potential important mechanism of action of glibenclamide could be the upregulation of cd200r1, as its agonist CD200FC significantly protected ganglion cells from apoptosis in a nerve crush model. 54 The up-regulation of Bcl2a1 gene, with a strong antiapoptotic effect is in line with this hypothesis.…”
Section: Discussionsupporting
confidence: 64%
“…Studies on mice lacking CD200 have reported heightened pro-inflammatory responses in experimental animal models of uveoretinitis and exudative form of age related macular degeneration (3840). Conversely, enhancement of CD200R signaling ameliorates pathological outcome in optic nerve injury and experimental autoimmune uveoretinitis animal models, suggesting that CD200-CD200R interaction could be an exploitable avenue for therapeutic intervention (39, 41).…”
Section: Microglia In the Healthy Retinamentioning
confidence: 99%
“…CD200, a member of the immunoglobulin superfamily, is widely expressed in neurons, astrocytes, and oligodendrocytes, whereas its receptor (CD200 receptor 1, CD200R1) is expressed in myeloid cells and microglia (the brain-resident myeloid cells) in rodents [12] and also highly expressed by neurons in human according to the Ben Barres database. The interaction between CD200 and CD200R1 is critical for inhibiting microglial activation and localized neuroinflammation during the pathological development of several brain diseases, including Parkinson's disease, optic nerve crush, and germinal matrix hemorrhage [13][14][15]. The CD200/CD200R signaling pathway also participates in synaptic plasticity.…”
Section: Introductionmentioning
confidence: 99%